The Role of Financial Performance in Mediating the Influence of Green Finance and Competitive Advantage on Company Value (Company Case Study Energy Sub-Sector in 2021-2023) - Muhammad Luthfi Faisal; Tona Aurora Lubis; Ahmad Nur Budi Utama (International Journal of Business and Quality Research, 2025)
This study aims to determine the influence of green finance and competitive advantage on company value through financial performance as a mediating variable in energy sub-sector companies listed on the Indonesia Stock Exchange in 2021-2023. There were 13 companies with 39 observations that met the criteria as a research sample. This study uses Structural Equation Model analysis based on Partial Least Square (PLS). The results of this study show that, green finance has a negative and significant effect on company value, competitive advantage has a positive and insignificant effect on company value, green finance has a positive and significant effect on financial performance, competitive advantage has a negative and significant effect on financial performance, financial performance has a positive and significant effect on company value, financial performance mediates the influence of green finance on the company's value positively and significantly, and financial performance can mediate the influence of competitive advantage on the company's value negatively and significantly